PENANGGULANGAN BENCANA BANJIR DALAM PERENCANAAN PEMBANGUNAN DI KABUPATEN KUDUS - Indah Kurniasih Pratiwi (IPEM 16 UMY 278, 2016)
According to Law No. 24 In 2007 the potential causes of the disaster in the territory of the Unitary State of Indonesia are grouped into three types of disaster, ie a natural disaster, non-natural disasters and social disasters. The flood disaster is a natural event that can result in loss of property and loss of life and infrastructure damage. The impact was also felt by people Kudus, Central Java. In order to provide protection and the right to be free of fear, threat, risk and impact of disasters. One form of central or local government responsibility in the implementation of disaster management ie disaster risk reduction (DRR) and DRR integration with the development program. It is intended that the programs wherever possible DRR integrated into development planning at central and local levels both in its medium, RKP, strategic plan, and working plan of the Ministry / Institution, RPJMD, RKPD, and plan on regional work units. Keywords : The Flood Disaster, Disaster Management, Development Planning.